2019
DOI: 10.1029/2019gl083420
|View full text |Cite
|
Sign up to set email alerts
|

Perspective on Landfalling Frequency and Genesis Location Variations of Southern China Typhoon During Peak Summer

Abstract: Increasing intense landfalling typhoons (LFTYs) are of great coastal threatens to southern China. However, changes in genesis location and landfalling frequency of western North Pacific (WNP) LFTY dedicated to southern China remain unclear. Here we identified such LFTYs during peak summer and found that most LFTYs formed south of 20°N and the LFTY genesis locations over southern WNP have also experienced a sharp interdecadal shift since 1998, which are mainly attributed to the large‐scale environment changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…The reason for focusing on this most recent period (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017) is also due to the data quality, since the data quality from the earlier period is not as reliable [19][20][21][22]. Also, 1998 is a meaningful year in the WNP, as PDO (Pacific decadal oscillation) also changed from the warm phase to the cold phase [23][24][25]. Therefore, starting from 1998 ensures that all analyses are performed within the same multi-decadal phase without introducing further complications.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for focusing on this most recent period (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017) is also due to the data quality, since the data quality from the earlier period is not as reliable [19][20][21][22]. Also, 1998 is a meaningful year in the WNP, as PDO (Pacific decadal oscillation) also changed from the warm phase to the cold phase [23][24][25]. Therefore, starting from 1998 ensures that all analyses are performed within the same multi-decadal phase without introducing further complications.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the change in steering flow may be linked to the western North Pacific subtropical high activity (Zhang et al ., 2019b). However, there are very small differences in steering flow between before and after the 500‐hPa wind field is removed, except a reduction of wind magnitude (figure not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The differences in the trend of severe landfall typhoons (SLTYs) may be partly attributed to the TC data sets without observed maximum sustained wind speeds when they made landfall in China before 1973 and the inhomogeneity occurred around 1972 (Ying et al, 2014). Recently, Zhang et al (2019a); Zhang et al, 2019b) found the genesis locations of landfall typhoons in southern China experienced an interdecadal northwestward shift since 1998, with only a slightly increasing trend.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the reported trends in landfalling TC activity in South China were divergent. Some studies (Zhang et al, 2012b;Li et al, 2017;Zhang et al, 2019) showed no significant trend in landfalling TC intensity or frequency in South China. Park et al (2014) suggested no trend in landing TC frequency but a downward trend in landfalling TC intensity in South China.…”
Section: Introductionmentioning
confidence: 99%